PENGARUH PAD, BELANJA MODAL, DAN PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN DI KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2018-2022 - Meida, Elina Alfin; Susilo (Journal of Development Economic and Social Studies, 2024)
This study aims to analyze the effect of Local Own-source Revenue, Capital Expenditure, and Economic Growth on Poverty in the Regency/City of Central Java Province in 2018-2022. This study uses a quantitative approach with multiple linear regression analysis methods. The data obtained in this study are secondary data sourced from the website of the Central Statistics Agency (BPS), DJPK Ministry of Finance, as well as related publications. The type of data in this study is the panel data, which is a combination of time series data and cross section data. Data time series in the form of the 2018-2022 fiscal year, while the cross section data is in the form of 35 regencies/cities in Central Java Province. The results of this study were that PAD had a significant positive effect on poverty, capital expenditure had no effect on poverty, and economic growth had a significant negative effect on poverty.